2015
DOI: 10.5935/1806-6690.20150061
|View full text |Cite
|
Sign up to set email alerts
|

Allometric model for estimating leaf area in clonal varieties of coffee (Coffea canephora)

Abstract: The evaluation of leaf area is required in several agronomic studies given their importance to assess the plant growth. The objective of this study was to use statistical models to estimate leaf area of five clonal varieties of coffee (Coffea canephora) from linear dimensions (length and width maximum). Were used in the studies five varieties of Coffea canephora Pierre ex Froehner: Emcapa 8111, Emcapa 8121 Emcapa 8131, Emcapa 8141 and at Incaper 8142. The results obtained in this study allow us to conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 10 publications
4
23
0
7
Order By: Relevance
“…Thus, it is indicated that the models of dwarf pigeon pea leaf area estimation in function of the product of the central leaflet length times the width should be preferentially used when the higher accuracy is the objective in relation to the other models that are based only on length or width of the central leaflet, as confirmed by Schwab et al (2014) and Schmildt et al (2015). However, the power model based on the width of the central leaflet can be used, with a small reduction of accuracy, but being less laborious, since only one measured variable is required.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, it is indicated that the models of dwarf pigeon pea leaf area estimation in function of the product of the central leaflet length times the width should be preferentially used when the higher accuracy is the objective in relation to the other models that are based only on length or width of the central leaflet, as confirmed by Schwab et al (2014) and Schmildt et al (2015). However, the power model based on the width of the central leaflet can be used, with a small reduction of accuracy, but being less laborious, since only one measured variable is required.…”
Section: Resultsmentioning
confidence: 97%
“…Foliar area estimation models based on more than one measure are more notorious, according to those proposed for several species as Jatropha curcas (Pompelli et al, 2012), Passiflora spp. (Morgado et al, 2013), Vitis vinífera L. (Buttaro et al, 2015), Coffea canephora (Schmildt et al, 2015) and Prunus armeniaca L. (Cirillo et al, 2017), concluding that the best adjustments were found relating L and W in comparison with models that take into account only one dimension.…”
Section: Resultsmentioning
confidence: 99%
“…'Triunfo'. It should be emphasized as described by Schmildt et al (2015), for the determination of models that estimate the leaf area is necessary the destruction of the leaves, however after establishing the equation the leaf area can be estimated by obtaining the length along the main vein and the largest width of the leaf blade, with simple equipment such as ruler and or tape measure, non-destructively.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical models for estimating leaf area have already been developed for various crops, such as Cucumis melo L. [6], Crambe abyssinica [7], Jatropha curcas [4], Passiflora spp. [8], Coffea canephora [9], Vitis vinífera L. [10], Passiflora mucronata [11], Annona cherimila Mill. [12], Crotalaria juncea [5], Litchi chinensis Sonn.…”
Section: Introductionmentioning
confidence: 99%